Does Corporate Governance Affect Firm Performance? Empirical Evidence Based on the BSE 200 Index - Laskar, Najul; Debnath, Pranesh; Gunardi, Ardi (Indonesian Journal of Sustainability Accounting and Management, 2022)
Considering the endogeneity problem, this study investigates the impact of corporate governance attributes (CG) on firm performance in the Indian context. The sample of the study includes 174 companies listed on the Bombay Stock Exchange and the study period is eight years (2011–12 to 2018– 19). This study is based on secondary data obtained from published annual reports (for CG data) and the Capitalineplus database (for accounting data). Based on the regression models (i.e., Ordinary Least Squares model and Two Stage Least Square model), the study shows that almost all CG attributes such as board size, gender diversity, CEO duality, and board independence are significantly associated with firm performance. We also find that the control variables such as firm size, debt, and R&D spending are also significantly associated with firm performance. This study is the first of its kind to focus exclusively on the attributes of market capitalization and corporate governance in an emerging market like India. These new insights into this relationship provide useful information to the government, academics, policymakers, and other stakeholders.